Matrix metalloproteinase 9 production by monocytes is enhanced by TNF and participates in the pathology of human cutaneous Leishmaniasis. - Taís M Campos; Sara T Passos; Fernanda O Novais; Daniel P Beiting; Rúbia S Costa; Adriano Queiroz; David Mosser; Phillip Scott; Edgar M Carvalho; Lucas P Carvalho (Public Library of Science (PLoS), 2014)
INTRODUCTION:Cutaneous leishmaniasis (CL) due to L.braziliensis infection is characterized by a strong inflammatory response with high levels of TNF and ulcer development. Less attention has been given to the role of mononuclear phagocytes to this process. Monocytes constitute a heterogeneous population subdivided into classical, intermediate and non-classical, and are known to migrate to inflammatory sites and secrete inflammatory mediators. TNF participates in the induction of matrix metalloproteinases (MMPs). MMP-9 is an enzyme that degrades basal membrane and its activity is controlled by the tissue inhibitor of metalloproteinase. METHODS:Mononuclear cells were obtained from ex-vivo labeling sub-populations of monocytes and MMP-9, and the frequency was determined by flow cytometry. Culture was performed during 72 hours, stimulating the cells with SLA, levels of MMP-9 and TIMP-1 in the supernatants were determined by ELISA. RESULTS:We observed that cells from CL lesions secrete high amounts of MMP-9 when compared to healthy subjects. Although MMP-9 was produced by monocytes, non-classical ones were the main source of this enzyme. We also observed that TNF produced in high level during CL contributes to MMP-9 production. CONCLUSIONS:These observations emphasize the role of monocytes, TNF and MMP-9 in the pathogenesis of L. braziliensis infection.